MODELAGEM ESTRUTURAL, SÍNTESE E CARACTERIZAÇÃO DO COMPOSTO HÍBRIDO HIDROTALCITA-HIDROXIAPATITA - KAWAHARA, Creuza Kimito Caceres; BARBOSA, Graciele Vieira; OLIVEIRA, Lincoln Carlos Silva de; AMORESI, Rafael Aparecido Ciola; ZAGHETE, Maria Aparecid; CAVALHEIRO, Alberto Adriano (ANAIS DO ENIC, 2018)
-